Early relationships and paranoia: Qualitative investigation of childhood experiences associated with the development of persecutory delusions. (30th April 2016) - Dickson, Joanne M.; Barsky, Jamie; Kinderman, Peter; King, David; Taylor, Peter J.
Abstract: Research suggests a link between Persecutory Delusions (PDs) and early interpersonal difficulties. However, little research has explored the first-hand experience of navigating such adversities in those who later developed PDs. The current study reports on a qualitative investigation of the early interpersonal experiences and challenges faced by a sample of individuals who have recovered from PDs, using a semi-structured interview. A sample of seven individuals who have previously experienced PDs were recruited from two National Health Services (NHS) and an Early Intervention Psychosis service in England. Using an Interpretative Phenomenological Analytic (IPA) approach, the analysis identified three main themes (early experiences, impact of early experiences, coping with adversity). Early experiences captured early inconsistent and problematic relationships in childhood, and experiences of victimization. Exploring the impact of these early events revealed important roles for the participants' inconsistent sense of self, their negative perception of others, and their disturbed social functioning and substance use. Coping with adversity revealed distinct forms of avoidant and proactive coping. The findings are consistent with models of PDs that emphasise the impact of early interpersonal experiences, and offer support for attachment and cognitive factors. Highlights: Early interpersonal adversity was present in those with past persecutory delusions. These experiences may account for the development of persecutory delusions. These early experiences were linked to changes in self-concept. Both proactive and avoidant coping was reported.